(untitled) (World Bulletin of Education and Learning, 2025)
The article presents the history of folklore art, its stages of development, and its origins. Mainly, the creative research of Fayzulla Karomatli, his place in Uzbek musical art. Folklore is considered an oral art, which is a collection of works that reflect the values, customs, traditions, lifestyle, work activities of a particular nation, inherited from ancestors to generations for centuries, in short, its entire identity.